2013
DOI: 10.1136/bcr-2013-010326
|View full text |Cite
|
Sign up to set email alerts
|

Spinal osteomyelitis due toMycobacterium fortuitumin a former intravenous drug user

Abstract: A 47-year-old woman with a history of intravenous drug use presented to the emergency department with a 6-month history of pain in her lumbar back and right buttock. She had stopped injecting drugs 1 year ago. Physical examination was unremarkable except for paraspinal and right sacroiliac joint tenderness. MRI confirmed discitis, osteomyelitis and abscess formation in the L5-S1 disc space. She underwent extensive vertebral surgery and debridement of the spinal abscess. Her surgical cultures grew Mycobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…This is particularly due to the introduction of bacteria into the venous circulation or subcutaneous tissue, which is common among those who inject drugs [2,3]. Multiple studies have indicated increasing rates of infective endocarditis [4][5][6][7], osteomyelitis [3,[8][9][10][11][12][13][14][15], and septic arthritis associated with intravenous drug use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly due to the introduction of bacteria into the venous circulation or subcutaneous tissue, which is common among those who inject drugs [2,3]. Multiple studies have indicated increasing rates of infective endocarditis [4][5][6][7], osteomyelitis [3,[8][9][10][11][12][13][14][15], and septic arthritis associated with intravenous drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with opioid use disorder (OUD) have an increased risk of acquiring deep tissue infections due to the high prevalence of subcutaneous injections [3,[8][9][10][11][12][13][14][15][16][17][18][19][20]. OUD rates have risen to epidemic proportions in many communities in Ontario.…”
Section: Introductionmentioning
confidence: 99%
“…10 Interestingly, NTMB-associated infection has been shown to cause insidious seeding of the spine even years after a patient's last IVDU, which suggests the possibility of a latent infection and transient bacteremia that can occur at a later time. 11 It is very likely in a young, immunocompetent patient with no other comorbidities that the infection was due to a recent history of IVDU, potentially due to poor hygienic practices.…”
Section: Resultsmentioning
confidence: 99%
“…fungal, mycobacterial, nocardial, and Brucella species are identified in rare cases involving patients with intravenous drug abuse. 1,3,7,11,15 Prolonged antibiotic therapy, for at least 6-8 weeks if the infection is bacterial or lifelong if it is fungal or mycobacterial, is indicated in these patients. However, despite aggressive treatment, relapse of infection and patient death have been reported in up to 32% and 6%-15% of cases, respectively.…”
mentioning
confidence: 99%